Effectiveness of Low-Dose Continuous Gaseous Ozone in Controlling Listeria innocua on Red Delicious Apples During 9-Month Commercial Cold Storage - Shen, Xiaoye; Su, Yuan; Hua, Zi; Sheng, Lina; Mendoza, Manoella; He, Yang; Green, Tonia; Hanrahan, Ines; Blakey, Rob; Zhu, Mei-Jun (Frontiers in Microbiology, 2021)
This study aimed to investigate the effects of low-dose continuous ozone gas at different concentrations in controlling Listeria innocua and quality attributes and disorders of Red Delicious apples during long-term commercial cold storage. Red Delicious apples were inoculated with a three-strain L. innocua cocktail at ~6.2 log10 CFU/apple, treated with or without 1-methycyclopropene, and then subjected to controlled atmosphere (CA) storage with or without continuous gaseous ozone in a commercial facility for 36 weeks. Uninoculated Red Delicious apples subjected to the above storage conditions were used for yeast/mold count and quality attributes evaluation. The 36-week of refrigerated air (RA) or CA storage caused ~2.2 log10 CFU/apple reduction of L. innocua. Ozone gas application caused an additional >3 log10 CFU/apple reduction of L. innocua compared to RA and CA storage alone. During 36-week CA storage, low-dose continuous gaseous ozone application significantly retarded the growth of yeast/mold, delayed apple firmness loss, and had no negative influence on ozone burn, lenticel decay, russet, CO2 damage, superficial scald, and soft scald of Red Delicious apples compared to CA alone storage. In summary, the application of continuous low-dose gaseous ozone has the potential to control Listeria on Red Delicious apples without negatively influencing apple quality attributes.